THU0082 Induction of adjuvant arthritis in the male lewis rat: lipoidal amine exhibits an "all-or-nothing" threshold response distinct from the mycobacterial linear dose response. (1st June 2001) - Feige, U; King, C; Bolon, B
Abstract : Background: Marked polyarthritis can be induced in male Lewis rats by injection of either heat-killed Mycobacterium tuberculosis (H37Ra, Difco) in paraffin oil (AdA) or lipoidal amine in complete Freund's adjuvant (LA/CFA). Objectives: The present study examined whether or not the disease severity in these two models is related to the dose of the inciting agent. Methods: Adjuvant arthritis was induced in male Lewis rats (190 to 240 g) by administration of M. tuberculosis (AdA; 1.25, 2.5, 5, 10, 20 or 40 mg/ml) or lipoidal amine (LA/CFA; 4, 6.25, 12.5, 25, 50, 100, 200, or 400 mg/ml). The clinical evaluation included measurements of body weight and hind paw volume (by water plethysmography) on day 0 and then daily between days 8 to 16. At necropsy on day 16, inflammation (by histopathology) and bone integrity (bone mineral density [BMD] by DEXA; histopathology) were assessed in the tibiotarsal (hock) and femorotibial (knee) joints. Results: Induction of AdA followed a typical dose-response curve for most parameters, including body weight, loss of BMD (hock and knee), inflammation (paw volume and histopathology), and bone erosion (histopathology). In contrast, LA/CFA exhibited an "all-or-nothing" response with a threshold for activity of 50 mg/ml. The severity of arthritis (measured both clinically and morphologically) was comparable at day 16 for AdA engendered by > 1.25 mg/ml of mycobacteria and LA/CFA induced by > 50 mg/ml. These data indicate that AdA and LA/CFA exhibit different dose-response patterns. Conclusion: The practical implication of this finding is that AdA will be the better adjuvant arthritis model for investigating the biology and treatment of inflammatory joint disease over a range of lesion severities.